ANALYSIS OF FADIL JAIDI’S PERSONAL BRANDING AS A CONTENT CREATOR ON INSTAGRAM AND YOUTUBE - dennis Dennis Said (Jurnal Komunikasi Korporasi dan Media (JASIMA), 2022)
The rise of emerging content creators is the impact of technological developments on social media platforms, especially Instagram and YouTube. Instagram and YouTube are the most accessed platforms from 2020-2021. This is a demand for content creators in creating quality and creative works and content so as to form personal branding, in order to compete for attention and recognition from social media users. This research will reveal the personal branding of an influencer as well as a content creator on Instagram and Youtube, namely Fadil Jaidi. The concept used is the concept of the eight laws of personal branding (Peter Montoya, 2002) consisting of Specialization, Leadership, Personality, Difference, Appearance, Firmness, Unity and Good Intentions. . If you look at the activities carried out by Fadil Jaidi, everything he does is inseparable from his personal branding, from the unique endorsement method to the content that is made out of the box.